2020
DOI: 10.18378/rvads.v15i1.6494
|View full text |Cite
|
Sign up to set email alerts
|

Verde urbano na conservação da biodiversidade em João Pessoa, Paraíba

Abstract: O crescimento urbano tem alterado cada vez mais às características naturais dos ecossistemas em áreas povoadas, resultando na redução de áreas naturais e de biodiversidade. Para minimizar os impactos negativos da expansão urbana são criadas as áreas verdes e áreas protegidas. Neste contexto, este estudo objetivou analisar a importância do verde urbano existente na área urbana do município de João Pessoa, Paraíba, para a conservação da biodiversidade em um aglomerado populacional. O método consistiu na pesquisa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
1
0
3
Order By: Relevance
“…However, the surrounding urban matrix in both parks seems to have contributed to the presence of several common species between them, even considering the distance of approximately 7.5 km, suggesting that their urban surroundings favor the presence of these species in the considered regions. Araújo and Moreira (2020) have demonstrated that urban forests play an important role in stabilizing and maintaining the diversity of trees that exist within the city environment. The main benefits in which urban parks provide are precisely comfort and microclimate changes (Graça and Telles, 2020).…”
Section: Species Richness and Abundancementioning
confidence: 99%
“…However, the surrounding urban matrix in both parks seems to have contributed to the presence of several common species between them, even considering the distance of approximately 7.5 km, suggesting that their urban surroundings favor the presence of these species in the considered regions. Araújo and Moreira (2020) have demonstrated that urban forests play an important role in stabilizing and maintaining the diversity of trees that exist within the city environment. The main benefits in which urban parks provide are precisely comfort and microclimate changes (Graça and Telles, 2020).…”
Section: Species Richness and Abundancementioning
confidence: 99%
“…Espaços verdes urbanos como parques e jardins, são grandes contribuintes para o equilíbrio ambiental nas cidades. Além da clara importância para o lazer e contemplação necessários para a qualidade da saúde humana (WHO 2016), são considerados importantes reservatórios de fauna, incluindo tanto espécies nativas como introduzidas (Pasqual & Fachini 2008;Gomes 2014;Alexandre et al 2017;Araújo & Moreira 2020;Sousa et al 2021).…”
Section: Introductionunclassified
“…Faz-se necessário esclarecer que não se pretende afirmar, nesse estudo, que os títulos aqui elencados representam todo o universo de leitura na província da Paraíba, em 1864, mas que estes se constituíram como instrumentos para divulgação de saberes, por meio dos impressos nas páginas d'O Publicador. É relevante afirmar, ainda, que O Publicador foi o primeiro jornal de impressão diária na província e um dos mais longevos da Paraíba, durante o Império, circulando de 1862 até o ano de 1886 (ARAÚJO, 1986).…”
unclassified